Focus on renewable energy sources - Scandurra, Giuseppe (Renewable energy: research, development and policies, 2018)
"Countries tend to contrast these limits to growth using a higher percentage of renewable sources for electricity generation, though the technological limits still suffer. Renewable energy sources are appreciated worldwide for their ability to limit significantly the impact of anthropic activities on energy production and counter the gradual appreciation of the raw materials used in the process of traditional generation based on gas and/or oil power plants. Moreover, renewable generation can encourage off-grid generation in the underdeveloped countries. The attention to environmental issues has led several countries to ratify international agreements such as the Kyoto Protocol, Durban Protocol and, more recently, the Paris Agreement; these mandates pledge to reduce emissions of pollutants and to increase the share of energy produced through the use of renewable sources, but the results obtained so far are not encouraging. The relevance of the renewable energy generation and the increase in the investments in a newly installed capacity lead many scholars to investigate the relationship between economic growth and the key factors of the investments in RES. With this volume, the authors want to explore and analyze the causes and consequences of fragmentation and discussing policy responses on promoting renewable energy generation by shedding light on the policies proposed to promote the renewable generation and enhance energy efficiency, their effectiveness in reducing environmental degradation and the promotion of decarbonization, and discussing how developing countries do and should continue to invest in green generation"--